The Impact of International Trade on a Country's Economy - Jabborova Elinoza; Sherkhon Rashidov (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
Abstract: This article explores in detail how international trade affects acountry’s economy. It examines how export and import activities influence economic growth, job creation, technology transfer, and investment flows. Both the positive and negative aspects of trade are discussed, including market stability and the role of global cooperation. The study shows that international trade is a critical factor in enhancing economic stability and accelerating development.